The Flexible Work Practices and Employee Performance: An Empirical Study on Productivity Outcomes - Vidi Paramestri, Nabila; Arifianti, Ria; Meisa Dai, Ratna (Universitas Yudharta Pasuruan, 2025)
Introduction: This study aims to determine the influence of Flexible Working Arrangement (FWA) on employee productivity, particularly among employees in the lifestyle category at PT X. In the context of evolving workplace trends, FWA is seen as a strategic approach to enhance productivity, efficiency, and work satisfaction. Method: The research employs a quantitative method with a descriptive-verificative approach. Data were collected through observation, interviews, and the distribution of questionnaires to 71 respondents. The sampling technique used is the saturated sampling method. The data were analyzed using simple linear regression. Result: The results show that the Flexible Working Arrangement has a positive and significant effect on employee productivity. The analysis revealed a coefficient of determination (R²) of 36.48%, indicating that FWA explains approximately one-third of the variance in employee productivity. The remaining 63.52% is likely influenced by other factors not explored in this study. Conclusion: The findings suggest that Flexible Working Arrangement plays a role in enhancing employee productivity at PT X, particularly within the lifestyle category. However, other factors outside of FWA also contribute to productivity outcomes and should be explored in future research.